2007
DOI: 10.1016/j.marenvres.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia in the East China Sea: One of the largest coastal low-oxygen areas in the world

Abstract: Anoxia and hypoxia have been widely observed in estuarine and coastal regions over the past few decades; however, few reports have focused on the East China Sea (ECS). In June and August 2003, two cruises sampled at stations covering almost the entire shelf of the ECS to examine hypoxic events and their potential causes. In August, DO concentrations <2-3 mg l(-1) covered an area estimated at greater than 12,000 km(2) (or 432 km(3) volume). In contrast, water column DO concentrations exceeded 4 mg l(-1) through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
138
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(155 citation statements)
references
References 39 publications
9
138
0
1
Order By: Relevance
“…Approximately 2.3 9 10 9 kg of N and 0.2 9 10 9 kg of P were transported by the Yangtze River over a year from May 1998 to April 1999 (Duan et al 2008). The large quantity of nutrient inputs from rivers and their ratios may cause elevated primary production, frequent harmful algae blooms and a large area of hypoxia in the Yangtze Estuary and the ECS (Li et al 2002;Wang 2006;Chen et al 2007;Zhou et al 2008). Therefore, nutrient cycles in the Yangtze River Basin has recently attracted increasing attention of many researchers, the public and decision makers (Duan et al 2000a(Duan et al , b, 2008Xing and Zhu 2002;Shen et al 2003;Yan et al , 2010Liu et al 2003;Huang et al 2006;Cai 2006;Sun 2010;Yang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2.3 9 10 9 kg of N and 0.2 9 10 9 kg of P were transported by the Yangtze River over a year from May 1998 to April 1999 (Duan et al 2008). The large quantity of nutrient inputs from rivers and their ratios may cause elevated primary production, frequent harmful algae blooms and a large area of hypoxia in the Yangtze Estuary and the ECS (Li et al 2002;Wang 2006;Chen et al 2007;Zhou et al 2008). Therefore, nutrient cycles in the Yangtze River Basin has recently attracted increasing attention of many researchers, the public and decision makers (Duan et al 2000a(Duan et al , b, 2008Xing and Zhu 2002;Shen et al 2003;Yan et al , 2010Liu et al 2003;Huang et al 2006;Cai 2006;Sun 2010;Yang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Coastal waters can be susceptible to upwelling of hypoxic water from elsewhere, as in the California Current system off the west coast of North America (Grantham et al 2004;Bianucci and Denman 2012), or to a change in stratification due to winter warming of surface water, as has been observed in the Japan Sea (Kang et al 2004). In some coastal areas, such as the East China Sea (Chen et al 2007), South China Sea (Dai et al 2006), Gulf of Mexico (Rabalais et al 2001), and the lower Saint Lawrence estuary (Gilbert et al 2010), physical circulation has contributed the conditions necessary to support deoxygenation, while eutrophication caused by the discharge of municipal wastewater or agricultural runoff (Falkowski et al 2011) has provided a local stress that has pushed these areas into hypoxia.…”
mentioning
confidence: 99%
“…Combining the above-mentioned data and discussions, it could be concluded that the enrichment of inorganic N and Si may enhance acidification in the SWLZB. Acidification is often accompanied with lower dissolved oxygen concentration, a common phenomenon of acidified regions related to eutrophication caused by nutrient enrichment (Chen et al, 2007;Gilbert et al, 2010), which in turn facilitates sediment nutrient release. Sediment nutrient release may further stimulate algal blooms, leading to a positive feedback loop that perpetuates blooms and eutrophication, subsequently to acidification.…”
Section: Nutrient Distribution and Acidificationmentioning
confidence: 99%